Inter-comparison of the GCOM sea ice product on the Arctic ocean - Shimada, Rigen; Kurihara, Yukio; Yoshizawa, Eri (2023)
The 14th Symposium on Polar Science/Interdisciplinary sessions [IA] Arctic Research, Thu. 16 Nov. / Entrance Hall (1st floor), National Institute of Polar Research conference object